2022
DOI: 10.1530/ec-21-0379
|View full text |Cite
|
Sign up to set email alerts
|

Low health-related quality of life in hypoparathyroidism and need for PTH analog

Abstract: Objective: Hypoparathyroidism (HypoPT) is a rare endocrine disorder in which insufficient levels of parathyroid hormone (PTH) lead to low serum calcium levels and muscular cramps. The aim was to study the Health-Related Quality of Life (HRQoL) and comorbidities in patients with HypoPT compared with the general population and estimate the need of treatment with PTH-analogue. Design: Patients with HypoPT were identified and compared with a population sample. Short Form-36 (SF-36) and EuroQol-5 Dimensions Visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…A systematic review of more than 372 studies 25 identified only five studies assessing quality of life in patients with hypoparathyroidism 19,23,[26][27][28] , all of which reported low QoL in this population. Other recent studies also demonstrate that hypoparathyroidism is a disease that negatively affects QoL [29][30][31][32] . Seven of the studies assessed QoL with the SF-36 19,[26][27][28][29][30][31] ; the scores obtained were compared against the normative reference range in four of these studies 19, 27, 28, Astor et al 19 , Cusano et al 28 and Kontogeorgos et al 31 demonstrated that the presence of hypoparathyroidism affected all eight SF-36 domains.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A systematic review of more than 372 studies 25 identified only five studies assessing quality of life in patients with hypoparathyroidism 19,23,[26][27][28] , all of which reported low QoL in this population. Other recent studies also demonstrate that hypoparathyroidism is a disease that negatively affects QoL [29][30][31][32] . Seven of the studies assessed QoL with the SF-36 19,[26][27][28][29][30][31] ; the scores obtained were compared against the normative reference range in four of these studies 19, 27, 28, Astor et al 19 , Cusano et al 28 and Kontogeorgos et al 31 demonstrated that the presence of hypoparathyroidism affected all eight SF-36 domains.…”
Section: Discussionmentioning
confidence: 92%
“…Brazilian Journal of Health Review, Curitiba, v. 6, n. 2, p. 6018-6033, mar./apr., 202331 and against a control group in three of them26,29,30 . When compared with normative data,…”
mentioning
confidence: 99%
“…Akibat dari berkurangnya produksi PTH ialah ketidakmampuan tubuh untuk mempertahankan normokalsemia dan normofosfatemia. Oleh karena itu, temuan biokimia yang ditemukan pada penyakit ini berupa hipokalsemia, hiperfosfatemia, dan PTH rendah (Bilezikia, 2020;Kontogeorgos et al, 2022).…”
Section: Pendahuluanunclassified
“…Hypoparathyroidism (HPt) is a rare endocrine disorder responsible for hypocalcemia and hyperphosphatemia due to insufficient levels of parathyroid hormone (PTH) [ 1 ]. The most common causes of HPt are postsurgical complications, genetic or autoimmune diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%